2018
DOI: 10.3892/ol.2018.8718
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin�D and DDX4 regulate the proliferation and invasion of ovarian cancer cells

Abstract: Ovarian cancer is one of the most commonly occurring types of cancer and one of the most common causes of cancer-associated mortality in women. Diagnosis of ovarian cancer at an early stage is difficult due to the lack of specific symptoms. In the present study, it is demonstrated that active vitamin D treatment prohibited the proliferation and invasion of ovarian cancer cells, and the expression level of a germ cell specific marker DEAD (Asp-Glu-Ala-Asp)-box helicase 4 (DDX4), which is overexpressed in ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…As for DDX4, it presents in gonadal germ cells in both fetal and adult. DDX4 is abundant mostly in mature, as known, oocytes and spermatocytes and play a vital role in germ line cells development in ovary [ 52 ]. VEGFA is essential for both physiological and pathological angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As for DDX4, it presents in gonadal germ cells in both fetal and adult. DDX4 is abundant mostly in mature, as known, oocytes and spermatocytes and play a vital role in germ line cells development in ovary [ 52 ]. VEGFA is essential for both physiological and pathological angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…DDX4 (DEAD (Asp-Glu-Ala-Asp)-box helicase 4) has been found to be another target for active vitamin D [49]. Treatment with active vitamin D reduced the expression of DDX which inhibited the invasion of ovarian cancer cells [49].…”
Section: Epithelial-mesenchymal Transition and Cancer Progressionmentioning
confidence: 99%
“…DDX4 (DEAD (Asp-Glu-Ala-Asp)-box helicase 4) has been found to be another target for active vitamin D [49]. Treatment with active vitamin D reduced the expression of DDX which inhibited the invasion of ovarian cancer cells [49]. Microarray studies have identified a number of target genes involved in tumour growth and progression regulated by 1,25(OH) 2 D. The upregulation of lysophosphatidic acid G-protein coupled receptor (Edg2) is consistent with its function in the inhibition of tumour growth.…”
Section: Epithelial-mesenchymal Transition and Cancer Progressionmentioning
confidence: 99%
“…7 As an immune modulator, vitamin D3 has been found to be a factor in the prevention and mitigation of several forms of cancer including breast, ovarian, colorectal, oral, small-cell lung and prostate cancers. [8][9][10][11][12][13][14][15][16][17][18][19][20] The emerging evidence for the therapeutic use of vitamin D in the treatment of cancer warrants attention. 11,19,21,22 Cancer costs across the world are inestimable, and not all countries can afford to test and treat for the multiple cancers arising within the population.…”
Section: Introductionmentioning
confidence: 99%